Evaluation of the Modified Atkins Diet for the Treatment of Epileptic Spasms Refractory to Hormonal Therapy: A Randomized Controlled Trial. (July 2021) - Sharma, Suvasini; Goel, Shaiphali; Kapoor, Dipti; Garg, Divyani; Panda, Isha; Elwadhi, Aman; Patra, Bijoy; Mukherjee, Sharmila B.; Pemde, Harish
Objectives: We aimed to evaluate the efficacy of the modified Atkins diet in children with epileptic spasms who had failed hormonal therapy. Methods: Children aged 9 months to 3 years having daily epileptic spasms despite a trial of ACTH or oral prednisolone and 1 additional anticonvulsant medication were enrolled. Children were randomly assigned to receive the modified Atkins diet either immediately or after a delay of 4 weeks. The ongoing anticonvulsant medications were continued unchanged. The primary outcome variable was the proportion of children who achieved spasm freedom as per parental reports at 4 weeks. Secondary outcomes included time to spasm cessation, proportion of children with electroclinical remission, the proportion of children with >50% reduction of spasms at 4 weeks, and adverse effects of the diet. (ClinicalTrials.gov Identifier: NCT03807141). Results: A total of 91 children were enrolled in the study; 46 in the diet group and 45 in the control group. At the end of 4 weeks, 11 children in the diet group were spasm free compared with none in the control group ( P ≤ .001). The median time to achieve spasm cessation was 10 days (interquartile range 9-20). Nine of these had resolution of hypsarrhythmia on electroencephalography (EEG). Thirty (65.2%) in the diet group had >50% reduction in spasms, compared with none in the control group ( P < .001). The most common side effect was constipation, noted in 34.8% of the children. Conclusions: The modified Atkins diet was found to be effective and well tolerated in children with epileptic spasms refractory to hormonal therapy.